A Philosophical Study of The Existence of A Restorative Justice House As A Forum For Resolving Minor Criminal Cases In The Jurisdiction of The Palangka Raya District Attorney's Office - Kristanto, Kiki; Fransisco, Fransisco; Alfarizy, Tomy; Saputra, Fandra; Mawarni, Mira (Journal of Law, Politic and Humanities, 2024)
This study analyzes the existence of Restorative Justice House (Rumah Restoratif Justice) as a mechanism for resolving minor criminal cases in the jurisdiction of the Palangka Raya District Attorney's Office. The background of the problem shows an increase in the number of minor criminal cases resulting in excessive court workload and ineffective handling of conflicts in the society. In this context, Restorative Justice House emerges as an alternative solution that emphasizes restorative justice, where the main focus is the restoration of relationships between perpetrators, victims and the community. The purpose of this study is to evaluate the philosophical and practical role of Restorative Justice House in supporting the criminal justice system in Palangka Raya. This research seeks to answer the questions: What is the philosophical basis or main principle of the restorative justice house concept established by the Palangka Raya District Attorney's Office? What is the urgency of the existence of restorative justice houses in handling minor criminal cases in the jurisdiction of the Palangka Raya District Attorney's Office? The research method used was a qualitative approach with literature analysis and in-depth interviews with legal practitioners and communities involved in Restorative Justice House. The results of this study indicate that Restorative Justice House provides a practical solution to reduce the burden on the courts and strengthens the principles of restorative justice that are more inclusive and adaptive to local needs. The philosophical implications of Restorative Justice House underscore the importance of a restorative and rehabilitation-oriented approach, as opposed to a traditional retributive approach.